Development of a computer-based diagnostic system of children with speech problem - Yunus, Jasmy (Universiti Teknologi Malaysia, 2007)
The computer-based Malay Articulation-Phonological Assessment System (MAPAS) utilizes speech recognition techniques (Artificial Neural Networks and Linear Predictive Coding) in recognizing Malay speech sounds. So far computer-based Malay speech diagnostic system is not available and currently the practice is performed by a speech language pathologist. With MAPAS, the speech assessment could be conducted faster and in an objective way. During the speech assessment, the client just speak to the microphone and MAPAS will record and transcribe the speech sounds. Then the analysis is summarized in a click of time.